Acoustic performance of effervescent sprays by time–frequency method with different atomizer structures under different operating conditions. (June 2016) - Sun, Chunhua; Ning, Zhi; Lv, Ming; Yan, Kai; Fu, Juan
Highlights: A new observation on effervescent spray by acoustic method was established. Built the bridge between internal flow structure and spray acoustic performance. Effervescent spray unsteadiness under different conditions was evaluated by a new method. Abstract: The acoustic performance of effervescent sprays was experimentally investigated at various liquid flow rates and gas to liquid ratios (GLRs) by mass under pressure < 0.5 MPa. A transparent effervescent atomizer with different mixing chambers and exit orifices was used in the study. An unconventional description of spray characteristics under various internal flow regimes was obtained using the adaptive optimal kernel (AOK) spectrogram of the spray acoustic in the time–frequency domain. Acoustic energy was calculated using the Hilbert Huang transform (HHT) method, which provides a quantitative comparison of vibration intensity under different structures and operating conditions. A new evaluation of spray unsteadiness was established based on acoustic energy analysis. Results showed that gas flowing out of the orifice leads to an increase in the amplitude of high frequency components. The spray characteristics under different internal flow regimes could be reflected from the AOK spectrograms, through which a new perspective on effervescent sprays in the time domain is presented. Acoustic energy was mostly influenced by both the air flow rate and geometry of the exit orifice and showed reduced sensitivity to the structure of the mixing chamber. The structure of the atomizer affected the internal gas–liquid two-phase flow structures and further influenced spray steadiness. A study of the present condition revealed that a structure with a farther location of aerator holes and a small exit orifice diameter strengthens the stability of pray performance.